Molecular characterization of virulence genes and influence of Xanthium strumarium extract against two Enterobacter species isolated from some soil invertebrates : X. strumarium extract against two Enterobacter species - Hassan, Mohamed M.; Albogami, Bander; Mwabvu, Tarombera; Awad, Mohamed F.; Alorabi, Jamal A. Alorabi; Montaser M. Hassan; Helal F. Al-Harthi; Roqayah H. Kadi; Almohaimeed, Hailah M. (Cellular and Molecular Biology, 2024)
The development of bacterial antibiotic resistance poses a danger to healthcare systems worldwide. To reduce the spread of disease, researchers are looking for novel measures to control bacterial infections to reduce the spread of disease. The antibacterial properties of Xanthium strumarium methanolic and ethanolic extracts were evaluated against Enterobacter cloacae and E. hormaeche isolated from some invertebrates (Porcellio laevis, Armadillidium sp. (isopods), and Archispirostreptus syriacus). All Enterobacter strains tested positive for the presence of the virulence genes csgA, csgD, AcrAB, fimH, and Hsp60. Extracts of X. strumarium had significant anti-biofilm activity against E. cloacae and E. hormaechei. The disruption of established biofilm growth by the plant samples proved to be effective against E. cloacae and E. hormaechei. Both E. cloacae and E. hormaechei showed inhibition of biofilm formation and promotion of biofilm eradication in response to X. strumarium extract. Phenolic compounds such as ferulic acid, chlorogenic acid, and trans-cinnamic acid, and flavonoids such as kaempferol were the most abundant components in the extract and might play crucial roles in the extract’s antibacterial and antibiofilm action. Results suggest that ethanolic leaf extracts from X. strumarium show potential as a novel approach to prevent infections caused by E. cloacae and E. hormaechei.